Seminar on the Role of Financial Management and Stress Management for Families during the Covid-19 Pandemic in Sindangsari Tangerang Village - Dhea Zatira; Amalia Indah Fitriana; Lisdewi Mulyati; Hendra Galuh Febrianto; Tekni Megaster (EQUATOR SINAR AKADEMIA, 2021)
The purpose of this activity is toexplain the impacts and remedies that occur due to the covid-19 pandemic, explain how to manage family finances,explain how to find sources of funds by utilizing the creativity we have,explain how to manage stress so th at it is not sustainable during a pandemic. covid-19, describes techniques that families can do to minimize stress. Conducted online via Zoom Meeting. The results of this activity There are still housewives who do not understand the importance of financial management and how to make a good financial budget, especially during a pandemic like today.